Optimization of combined in-vessel composting process and chemical oxidation for remediation of bottom sludge of crude oil storage tanks. Issue 20 (18th October 2018) - Koolivand, Ali; Naddafi, Kazem; Nabizadeh, Ramin; Saeedi, Reza
ABSTRACT: In this research, removal of petroleum hydrocarbons from oily sludge of crude oil storage tanks was investigated under the optimized conditions of in-vessel composting process and chemical oxidation with H2 O2 and Fenton. After determining the optimum conditions, the sludge was pre-treated with the optimum state of the oxidation process. Then, the determined optimum ratios of the sludge to immature compost were composted at a C:N:P ratio of 100:5:1 and moisture content of 55% for a period of 10 weeks. Finally, both pre-treated and composted mixtures were again oxidized with the optimum conditions of the oxidants. Results showed that total petroleum hydrocarbons (TPH) removal of the 1:8 and 1:10 composting reactors which were pre-treated with H2 O2 were 88.34% and 90.4%, respectively. In addition, reduction of TPH in 1:8 and 1:10 composting reactors which were pre-treated with Fenton were 83.90% and 84.40%, respectively. Without applying the pre-treatment step, the composting reactors had a removal rate of about 80%. Therefore, pre-treatment of the reactors increased the TPH removal. However, post-oxidation of both pre-treated and composted mixtures reduced only 13–16% of TPH. Based on the results, remarkable overall removal of TPH (about 99%) was achieved by using chemical oxidation and subsequent composting process. The study showed that chemical oxidation with H2 O2 followed by in-vessel composting is a viable choice for the remediation of the sludge.